Klänge in Bewegung Spurensuchen in Choreografie und Performance. Jahrbuch TanzForschung 2017 - Karoß, Sabine; Schroedter, Stephanie (Tanzforschung, 2019)
What happens when body and sound meet? The contributions to this volume track sound movements and the sound of movement.